The Influence of Principal Leadership and Teacher Professional Competence on the Quality of Elementary Schools - Suwarno Suwarno; Rasiman Rasiman; Soedjono Soedjono (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme)
This study investigates the influence of principal leadership and teacher professional competence on the quality of public elementary schools in Sumber District, Rembang Regency. Using a quantitative approach with an ex post facto correlational design, data were collected through validated questionnaires from 147 elementary school teachers selected via proportional random sampling from a population of 233 teachers across 25 schools. Data analysis employed SPSS 25 for Windows, including Pearson correlation, simple and multiple linear regression, t-test, F-test, and coefficient of determination (R²), all preceded by assumption tests (normality, linearity, multicollinearity). The results show that both principal leadership and teacher professional competence are significantly and strongly correlated with school quality (r = 0.623 and r = 0.606, respectively). Principal leadership explains 38.8% of the variation in school quality, while teacher professional competence contributes 36.7%. Combined, both variables account for 48.3% of the variance. The regression model confirms that improvements in both leadership and professional competence positively and significantly affect school quality. These findings highlight the essential role of effective leadership and teacher competence in enhancing educational outcomes. Therefore, systematic capacity-building for school leaders and continuous professional development for teachers are crucial strategies. This research contributes to empirical understanding and offers practical insights for policymakers, school administrators, and education stakeholders in formulating targeted interventions to improve school quality in primary education settings.